2023
DOI: 10.3390/biology12070973
|View full text |Cite
|
Sign up to set email alerts
|

Berberine and Its Study as an Antidiabetic Compound

Ayudiah Rizki Utami,
Iman Permana Maksum,
Yusi Deawati

Abstract: Diabetes mellitus (DM) is a metabolic disorder that causes hyperglycemia conditions and leads to various chronic complications that causes death. The prevalence of diabetes is predicted to continue to increase, and with the high toxicity levels of current diabetes drugs, the exploration of natural compounds as alternative diabetes treatment has been widely carried out, one of which is berberine. Berberine and several other alkaloid compounds, including some of its derivatives, have shown many bioactivities, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…(iii) Detailed information on Ber's mode of action, in comparison to archetypical c-I inhibitors, was obtained on the transcriptome and metabolome level. The redox-active compound was considered of high interest, as it emerged recently as a nutraceutical ingredient of food supplements meant to counteract aging and several diseases [89][90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Detailed information on Ber's mode of action, in comparison to archetypical c-I inhibitors, was obtained on the transcriptome and metabolome level. The redox-active compound was considered of high interest, as it emerged recently as a nutraceutical ingredient of food supplements meant to counteract aging and several diseases [89][90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…Fibre aids in digestion, regulates intestinal movements and can support the growth of beneficial gut bacteria, contributing to a healthy gut microbiome [49,50]. Some plant compounds, such as berberine from certain herbs, have shown potential to manage blood sugar levels and improving insulin sensitivity in individuals with type 2 diabetes [51,52]. It is impossible to list all the previously described compounds isolated from plants and their health-promoting properties, but continuously emerging scientific reports confirm the significant role of phytocomponents in the prevention of various conditions.…”
Section: Selected Plant Compounds and Disease Preventionmentioning
confidence: 99%
“…This imbalance between ROS and antioxidant dynamics culminates in cellular damage, dysregulated glucose homeostasis, and extensive detriment of organs and tissues [ 6 ], prompting explorations of the therapeutic potential of antioxidants [ 18 ]. Thus, several medicinal herbal remedies, including berberine [ 19 ], silymarin [ 20 ] and curcumin [ 12 ], among others, have been investigated for their potential in managing diabetic outcomes, although evidence on their safety and efficacy remains scarce [ 11 ]. Studies have demonstrated that medicinal plants show some activity of lowering blood glucose levels through mechanisms such as stimulating insulin production [ 21 ], improving insulin sensitivity [ 22 ], and inhibiting the intestinal enzyme amylase [ 23 ].…”
Section: Introductionmentioning
confidence: 99%